Association between body roundness index and obstructive sleep apnea: a cross-sectional study from the NHANES (2005–2008 to 2015–2020) - Ben Qin; Miao Shu; Song Cai; YaShi Zhou; JuKun Song; JuXiang Peng (BMC Oral Health)
Abstract Background Obstructive sleep apnea (OSA) is linked to obesity, and the body roundness index (BRI) is an innovative measure of obesity that more accurately reflects visceral and total body fat. The relationship between BRI and the likelihood of OSA is unclear, so we aimed to investigate the association between BRI and the prevalence of OSA. Methods We used data from the National Health and Nutrition Examination Survey (NHANES; 2005–2008 to 2015–2020) to conduct a cross-sectional study involving 24,476 individuals aged 18 years or older. OSA was assessed using three standardized NHANES questionnaire items measuring monthly daytime sleepiness, weekly apnea events, and habitual snoring frequency. A formula that uses the height and waist measures from the body measurements is used to calculate the BRI. Covariates, including sex, age, race/ethnicity, education level, marital status, poverty-income ratio (PIR), alcohol consumption, smoking status, high blood pressure (HBP), diabetes, and sleep duration were controlled using multivariate logistic regression models. Subgroup analyses, interaction tests, and smoothed curve fitting were also performed. Results After controlling for confounders, BRI showed a positive correlation with OSA. Among the 24,476 participants aged 18 and older, 11,856 were diagnosed with OSA. The full model revealed a significant positive association between BRI and OSA incidence (OR = 1.11, 95% CI: 1.08–1.14, p < 0.0001). Participants in the highest percentile of BRI had an 87% greater likelihood of developing OSA compared to those in the lowest percentile (OR = 1.87, 95% CI: 1.62–2.16, p < 0.0001). Conclusion BRI levels have shown a favorable correlation with the rising rates of OSA in the United States. The BRI serves as a straightforward anthropometric predictor of OSA.